A lagged response to the 11 year solar cycle in observed winter Atlantic/European weather patterns. Issue 24 (20th December 2013) - Gray, Lesley J.; Scaife, Adam A.; Mitchell, Daniel M.; Osprey, Scott; Ineson, Sarah; Hardiman, Steven; Butchart, Neal; Knight, Jeff; Sutton, Rowan; Kodera, Kunihiko
Abstract [1] The surface response to 11 year solar cycle variations is investigated by analyzing the long‐term mean sea level pressure and sea surface temperature observations for the period 1870–2010. The analysis reveals a statistically significant 11 year solar signal over Europe, and the North Atlantic provided that the data are lagged by a few years. The delayed signal resembles the positive phase of the North Atlantic Oscillation (NAO) following a solar maximum. The corresponding sea surface temperature response is consistent with this. A similar analysis is performed on long‐term climate simulations from a coupled ocean‐atmosphere version of the Hadley Centre model that has an extended upper lid so that influences of solar variability via the stratosphere are well resolved. The model reproduces the positive NAO signal over the Atlantic/European sector, but the lag of the surface response is not well reproduced. Possible mechanisms for the lagged nature of the observed response are discussed.